Climate mitigation potentials of teleworking are sensitive to changes in lifestyle and workplace rather than ICT usage - Tao, Yanqiu; Yang, Longqi; Jaffe, Sonia; Amini, Fereshteh; Bergen, Peter; Hecht, Brent; You, Fengqi (Proceedings of the National Academy of Sciences of the United States of America, 2023)
The growth in remote and hybrid work catalyzed by the COVID-19 pandemic could have significant environmental implications. We assess the greenhouse gas emissions of this transition, considering factors including information and communication technology, commuting, noncommute travel, and office and residential energy use. We find that, in the United States, switching from working onsite to working from home can reduce up to 58% of work’s carbon footprint, and the impacts of IT usage are negligible, while office energy use and noncommute travel impacts are important. Our study also suggests that achieving the environmental benefits of remote work requires proper setup of people’s lifestyle, including their vehicle choice, travel behavior, and the configuration of home and work environment.